The Blood-Cerebrospinal Fluid Barrier as a Potential Entry Site for the SARS-CoV-2 Virus - Solár, Peter; Šerý, Omar; Vojtíšek, Tomáš; Krajsa, Jan; Srník, Michal; Dziedzinská, Radka; Králík, Petr; Kessler, Markéta; Dubový, Petr; Joukal, Andrea; Balcar, Vladimir J; Joukal, Marek (Journal of medical virology, 2025)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is an RNA virus responsible for coronavirus disease 2019 (COVID-19). While SARS-CoV-2 primarily targets the lungs and airways, it can also infect other organs, including the central nervous system (CNS). The aim of this study was to investigate whether the choroid plexus could serve as a potential entry site for SARS-CoV-2 into the brain. Tissue samples from 24 deceased COVID-19-positive individuals were analyzed. Reverse transcription real-time PCR (RT-qPCR) was performed on selected brain regions, including the choroid plexus, to detect SARS-CoV-2 viral RNA. Additionally, immunofluorescence staining and confocal microscopy were used to detect and localize two characteristic proteins of SARS-CoV-2: the spike protein S1 and the nucleocapsid protein. RT-qPCR analysis confirmed the presence of SARS-CoV-2 viral RNA in the choroid plexus. Immunohistochemical staining revealed viral particles localized in the epithelial cells of the choroid plexus, with the spike protein S1 detected in the late endosomes. Our findings suggest that the blood-cerebrospinal fluid (B-CSF) barrier in the choroid plexus serves as a route of entry for SARS-CoV-2 into the CNS. This study contributes to the understanding of the mechanisms underlying CNS involvement in COVID-19 and highlights the importance of further research to explore potential therapeutic strategies targeting this entry pathway.
Keywords: dospělí; blood‐cerebrospinal fluid barrier; COVID‐19; Female; SARS-CoV-2; fosfoproteiny; Choroid Plexus; Adult; ženské pohlaví; RNA, Viral; lidé; koronavirové nukleokapsidové proteiny; Phosphoproteins; Coronavirus Nucleocapsid Proteins; Blood-Brain Barrier; Aged, 80 and over; COVID-19; mozek; neuroinvasion; hematoencefalická bariéra; Virus Internalization; RNA virová; plexus chorioideus; Male; Aged; Brain; Spike Glycoprotein, Coronavirus; SARS‐CoV‐2; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; internalizace viru; glykoprotein S, koronavirus; choroid plexus; Middle Aged; Humans